Detection of Epstein Barr Virus Infection in Reactive Arthritis Patients - Al-Bayati, Ola Hafedh Nsaif; Abood, Walaa Najm; Salloom, Dunya Fareed (Iraqi Journal of Science, 2020)
Reactive arthritis (ReA) is an incendiary joint inflammation that occurs few days to weeks after a gastrointestinal or genitourinary infection. The etiology of the disease is not well-known. Therefore, the present study included 80 females and 25 males, divided into 51 patients with reactive arthritis and 54 healthy individuals as control group. The study involved the detection of serum levels of anti-rheumatoid factor and anti-cyclic citrullinated peptide antibodies (anti-CCP) as well as those of CRP and C3 in all subjects. In addition, EBV levels were detected by Real Time-PCR technique. The results showed significantly increased levels (P < 0.05) of CRP, C3 and anti-CCP Ab in ReA patients’ group compared to the healthy control group (505.42 ± 402.94 versus 255.62 ± 135.5 U/ml, 61.20 ± 100.64 versus 20.43 ± 47.63 ng/ml and 35.11 ± 30.0 versus 6.82 ± 14.01 pg/ml, respectively), Also, the RF results demonstrated a significantly increased percentage in ReA patients’ group compared to a healthy control group (61.11 versus 37.25 %). While, the molecular study showed a non-significant increase in the percentage of EBV in ReA patients’ group compared to a healthy control group (17.65 versus 12.69 %). The results of this study lead to suggest that the immunological markers used may play a role in the development of ReA disease, while there was a non-significant association between EBV infection and ReA disease development.